2022
DOI: 10.1021/acsomega.2c01827
|View full text |Cite
|
Sign up to set email alerts
|

Cu/PCN Metal-Semiconductor Heterojunction by Thermal Reduction for Photoreaction of CO2-Aerated H2O to CH3OH and C2H5OH

Abstract: g-C 3 N 4 -based materials show potential for photoreduction of CO 2 to oxygenates but are subjected to fast recombination of photogenerated charge carriers. Here, a novel Cu-dispersive protonated g-C 3 N 4 (PCN) metal-semiconductor (m-s) heterojunction from thermal reduction of a Cu 2 O/PCN precursor was prepared and characterized using in situ X-ray diffraction, scanning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…As the results displayed in Figure a–c, the optimal concentration of Cu precursor solution is 5.1 mmol/L. Increasing the concentration of Cu precursor solution will increase the surface concentration of Cu active sites in the synthesized composites; however, a too high concentration of Cu precursor would lead to the aggregation of active components covering the active sites, in turn decreasing its catalytic performance . The results of temperature evaluation (Figure b) indicated that MeOH yield reached its highest value of 675 μmol·g –1 ·h –1 at 20 °C, which may be ascribed to the fact that low temperature is disadvantageous to the desorption of intermediates and/or products, while high temperature reduces the solubility of CO 2 in water and inhibits the adsorption of CO 2 on the catalyst surface .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…As the results displayed in Figure a–c, the optimal concentration of Cu precursor solution is 5.1 mmol/L. Increasing the concentration of Cu precursor solution will increase the surface concentration of Cu active sites in the synthesized composites; however, a too high concentration of Cu precursor would lead to the aggregation of active components covering the active sites, in turn decreasing its catalytic performance . The results of temperature evaluation (Figure b) indicated that MeOH yield reached its highest value of 675 μmol·g –1 ·h –1 at 20 °C, which may be ascribed to the fact that low temperature is disadvantageous to the desorption of intermediates and/or products, while high temperature reduces the solubility of CO 2 in water and inhibits the adsorption of CO 2 on the catalyst surface .…”
Section: Resultsmentioning
confidence: 91%
“…Increasing the concentration of Cu precursor solution will increase the surface concentration of Cu active sites in the synthesized composites; 70 however, a too high concentration of Cu precursor would lead to the aggregation of active components covering the active sites, in turn decreasing its catalytic performance. 71 The results of temperature evaluation (Figure 6b) indicated that MeOH yield reached its highest value of 675 μmol•g −1 •h −1 at 20 °C, which may be ascribed to the fact that low temperature is disadvantageous to the desorption of intermediates and/or products, while high temperature reduces the solubility of CO 2 in water and inhibits the adsorption of CO 2 on the catalyst surface. 72 A similar phenomenon was also found in the investigation of catalyst dosage (Figure 6c), which should be attributed to the lack of available catalytic sites when the catalysts are insufficient, whereas the shading effect of excessive catalysts is also detrimental to the reaction.…”
Section: Resultsmentioning
confidence: 95%
“…As shown in Figure 2 E, the binding energy peak of 284.9 eV was dominantly attributed to the C atom in surface aliphatic carbon (C‐C). 13 The binding energies of 400.68 and 532.28 eV were mainly attributed to the N and O elements in N‐H 14 and hydroxyl oxygen (C‐O), 15 respectively. The surface content of C atom was 89.03% in bared microspheres, while its content was gradually decreased in ibrutinib‐modified microspheres (84.38%) and NMDA‐2A‐modified microspheres (71.34%).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the introduction of Cu (metal, oxide, and quantum dots) as cocatalyst for heterostructures with various semiconductors (such as g-C 3 N 4 , TiO 2 , ZnV 2 O 4 , etc.) was demonstrated to effectively broaden the photoresponse range and effectively improve the PCO 2 RR activity/selectivity toward C 2+ compounds [119][120][121][122][123][124][125][126]. It is worth noting that despite metal copper itself does not have photocatalytic activity, it has high electrical conductivity, which may enhance the effectiveness of other photocatalysts when combined with them.…”
Section: Cu-based Heterojunctionsmentioning
confidence: 99%